PENGARUH KREDIBILITAS, CITRA MEREK, DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI PRODUK MAKE OVER DALAM PEMASARAN OMORFO SHOP PADA SHOPEE DI MAKASSAR - Dwita Ansir, Ratna; Romadhoni, Buyung; Indrayani, Syarthini (Politeknik Negeri Jakarta, 2025)
This study analyzes the influence of credibility, brand image, and consumer trust on purchase intention for Make Over products at Omorfo Shop on Shopee in Makassar. Using a quantitative approach and multiple linear regression analysis, the sample consists of 130 respondents who are active consumers of Omorfo Shop. The results indicate that brand image and consumer trust have a significant effect on purchase intention, while credibility does not show a significant partial effect. Data were analyzed using SPSS version 29.Keywords: Credibility, Brand Image, Consumer Trust and Purchase Intention